PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TIME TOKEN UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SEKOLAH DASAR - Firmala, Reny Citra (2016)
Penelitianinidilatarbelakangiolehrendahnyaaktivitasbelajarsiswapadasaatpembelajaran di kelas IVA salahsatu SD di KecamatanSukasari, Kota Bandung. Hal iniditandaidengansikap yang munculpadasaatpembelajaran. Penelitianinibertujuanuntukmendeskripsikanpeningkatanaktivitasbelajarsiswadenganmenerapkanlangkah-langkahpembelajarandalam model pembelajarankooperatiftipeTime Token. Metodepenelitian yang digunakanadalahpenelitiantindakankelasdengandesainKemmis&McTaggart.Penelitianinidilaksanakansebanyaktigasiklusdenganpartisipanpenelitiansebanyak 29 orang siswa. Instrumenpengungkap data yang digunakandalampenelitianiniyaitulembarobservasipenerapan model pembelajarankooperatiftipeTime Token, lembarobservasiaktivitasbelajarsiswa, dandokumentasi. Padasikluspertamacapaianaktivitasbelajarsiswasebesar 64%, kemudianpadasiklus IInaikmenjadisebesar82%, dannaikpadasiklus III menjadi 97%. Dari hasiltersebut, dapatdisimpulkanbahwapenerapan model pembelajarankooperatiftipeTime Tokendapatmeningkatkanaktivitasbelajarsiswasekolahdasar.;-- Image of this event will be based on Research by the low activity of student learning at the moment of learning in class IVA one elementary school in Sukasari, Bandung. It is characterized by an attitude that emerged at the time of learning. This study aims to describe the increase in student learning activities by implementing the measures in the model of cooperative learning, learning type Time Token. The research method used is the class action research with the design of Kemmis&McTaggart;. This research was carried out as many as three cycles with research participants as much as 29 students.The research instrument that had been use is the observation sheet application of cooperative learning model of type Time Token, the observation sheet learning activities of students, and documentation. On first cycle close to the student learning activities amounted to 64%, then in second cycle rose to 82%, then in the end of third cycle is97%. From these results, it can be concluded that the application of the cooperative learning model of type Time Token can enhance student learning activities of elementary school